Evaluation of Students' Experience at the Faculty of Education, Wadi Al-Shati University, in Using WhatsApp as an Interactive Educational Platform in Teaching (Sebha University Conference Proceedings, 2025)
The study aimed to evaluate the effectiveness of using WhatsApp as an interactive educational platform at Wadi Al-Shati University. The research relied on a questionnaire to collect data, with a sample of 150 students. The questionnaire was divided into five groups: the first group included personal questions about gender and age; the second group included statements about academic interaction; the third group included statements about improving academic achievement; the fourth group included statements about developing educational skills; and the fifth group included statements about student satisfaction.